Digital state in the context of legal reform in Ukraine: theoretical and legal aspect - E. Najafli (Law and Safety)
The purpose of the article is theoretical and legal coverage of the key parameters of legal reform in the field of digital state formation based on the application of the institutional approach, as well as taking into account the achievements of domestic theoretical and legal science and legal branch science. It is shown that the formation of a digital state is an integral element of digitalization of all spheres of social life and a requirement of modernity. Structural and procedural approaches to the study of legal reform in the field of digital state formation are analyzed. The expediency of combining these approaches for a deeper and more comprehensive scientific knowledge of the studied phenomenon is highlighted. It has been established that the legal reform in the field of the formation of a digital state should be recognized as a type of legal reform aimed at a holistic, comprehensive change in the conditions and legal basis of the organization and functioning of the state apparatus in the direction of its optimization and the widest application of information and communication technologies in order to simplify the state administration system, significantly increasing its effectiveness and including society and individual citizens in solving the most significant issues of social and state life. The key aspects and directions of this reform are analyzed.